Calcium Signaling in Oomycetes: An Evolutionary Perspective - Zheng, Limian; Mackrill, John J. (Frontiers in Physiology, 2016)
Oomycetes are a family of eukaryotic microbes that superficially resemble fungi, but which are phylogenetically distinct from them. These organisms cause major global economic losses to agriculture and fisheries, with representative pathogens being Phytophthora infestans, the cause of late potato blight and Saprolegnia diclina, the instigator of ‘cotton moulds’ in fish. As in all eukaryotes, cytoplasmic Ca2+ is a key second messenger in oomycetes, regulating life-cycle transitions, controlling motility and chemotaxis and, in excess, leading to cell-death. Despite this, little is known about the molecular mechanisms regulating cytoplasmic Ca2+ concentrations in these organisms. Consequently, this review analysed the presence of candidate calcium channels encoded within the nine oomycete genomes that are currently available. This revealed key differences between oomycetes and other eukaryotes, in particular the expansion and loss of different channel families, and the presence of a phylum-specific group of proteins, termed the polycystic kidney disease tandem ryanodine receptor domain (PKDRR) channels.